2007
DOI: 10.1166/jnn.2007.154
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Studies of a Self-Assembling Peptide Nanofiber Scaffold with Other Scaffolds

Abstract: A designer self-assembling peptide nanofiber scaffold has been systematically studied with 10 commonly used scaffolds in a several week study using neural stem cells (NSC), a potential therapeutic source for cellular transplantations in nervous system injuries. These cells not only provide a good in vitro model for the development and regeneration of the nervous system, but may also be helpful in testing for cytotoxicity, cellular adhesion, and differentiation properties of biological and synthetic scaffolds u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Comparison of Puramatrix functionality as a 3D environment for cell encapsulation has been previously demonstrated with other popular hydrogels. 40 Agarose has been frequently used as a 3D matrices to investigate neurite growth, although modification of agarose is necessary to obtain significant axon extension. 15 Matrigel has shown promise as a 3D matrix for neural growth and neuronal-astrocyte co-cultures, 13 but the presence of incompletely defined ECM proteins and cytokines in Matrigel may complicate studies of molecular neurite guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of Puramatrix functionality as a 3D environment for cell encapsulation has been previously demonstrated with other popular hydrogels. 40 Agarose has been frequently used as a 3D matrices to investigate neurite growth, although modification of agarose is necessary to obtain significant axon extension. 15 Matrigel has shown promise as a 3D matrix for neural growth and neuronal-astrocyte co-cultures, 13 but the presence of incompletely defined ECM proteins and cytokines in Matrigel may complicate studies of molecular neurite guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, poly(α-hydroxy acid) polymers including poly(glycolic acid) (PGA), poly(lactic acid) (PLA) and their copolymers (PLGA) have been seeded with rodent stem/progenitor cells (Vacanti et al, 2001;Teng et al, 2002;Bhang et al, 2007;Gelain et al, 2007). It was unknown, though, whether these types of polymers were compatible with hNSCs.…”
Section: Discussionmentioning
confidence: 99%
“…PF127, Matrigel and PuraMatrix hydrogels possessed this important characteristic. The biocompatibilities of PuraMatrix and Matrigel with rodent neural precursor cells were recently compared to other commonly used scaffolds including poly(α-hydroxy acid) polymers (Gelain et al, 2007). Although some differences were observed in cell viability and differentiation capacity, the compatibilities of the hydrogel materials and other scaffolds were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…These peptides include the arginine-alanine-aspartic acid-alanine repeat unit that gives the material the alternative name 'RADA' peptides [Gelain et al, 2007]. Ylä-Outinen et al [2014] showed that Puramatrix, at concentrations between 5 and 25 weight percent (wt%) in solution, supported not only the growth of neurons from human embryonic stem cells, but also some differentiation into glial cells.…”
Section: Tuned Materials Implanted In Cnsmentioning
confidence: 99%